Produção de açúcar invertido pelo uso de invertase imobilizada em resinas - Marquez, Líbia Diniz Santos (2007)
This work aims to offer a contribution for the development of the production of invert sugar by invertase immobilized on ion exchanging resins. The experiments were conduced in a batch stirred microreactor with temperature control and magnetic agitation. Firstly, kinetic assays on free invertase were conduced aiming to determine the hydrolysis kinetic and the best conditions of enzymatic activity and stability. The influences of pH and temperature were analyzed by a Central Composite Design (CCD) resulting in optimal values of 47ºC for temperature and 4.7 for pH. The soluble enzyme was stable from pH 5.5 to 7.5. The activation energy from the thermal deactivation process was 360 kJ/mol. The sucrose hydrolysis kinetic by free invertase fitted according substrate inhibition model with a kinetic constant (Km) of 45.2 mM and an inhibition constant (Ki) of 1.06 M. Invertase immobilization by adsorption on ion some exchange resins were then tested. After choosing Duolite A-568 as support, kinetic tests with the immobilized invertase were done. The study of the combined influence of temperature, pH and invertase concentration on immobilization medium was accomplished by a CCD, with an immobilization time of 24 hours, thus being obtained a temperature of 29ºC, a value of 5.0 for pH and an invertase concentration of 12.5 g/L as optimal conditions for immobilization process. The influences of temperature and pH in the enzymatic activity of immobilized invertase were studied by a CCD. The optimal temperature found was 40ºC and the pH presented little influence on the enzymatic activity. For the immobilized invertase, the stability in relation to the pH was restricted to an interval ranging from 5.5 to 6.0, a smaller range when compared to the enzyme free form. The activation energy from the biocatalyst thermal deactivation process was 415 kJ/mol, a higher value when compared with the free enzyme, showing that the immobilized enzyme is more sensible to temperature variations. The parameters found for the substrate inhibition model were a Vm of 0,047 Msac/min.gcat, a Km of 176 mM and a Ki of 1,08 M.